2017
DOI: 10.1099/jmm.0.000417
|View full text |Cite
|
Sign up to set email alerts
|

Molecular epidemiology of noroviruses detected in Vietnamese children with acute gastroenteritis from 2012 to 2015

Abstract: Noroviruses, an important cause of diarrhoea in humans, are genetically diverse. The recent norovirus seasons recorded the emergence of new recombinants of the capsid and polymerase genotypes, with a global dominance of GII.Pe_GII.4 Sydney 2012 and GII.P17_GII.17 in Asian countries. However, the number of papers reporting the distribution of both polymerase and capsid genotypes circulating among children is scarce, with none from Vietnam. This study described both the polymerase and capsid genotypes of norovir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 61 publications
5
16
0
Order By: Relevance
“…Norovirus was identified in 3.5% of the analyzed samples with severe AGE, whereas other reports indicated a prevalence of 5.3% in Mexico (29). Despite this, different studies showed the prevalence of this pathogen to be up to 35.2% in sporadic outbreaks of acute gastroenteritis in children under five-years-old (30). Indeed, the GII genogroup has been found in up to 92% of the analyzed samples in other countries (30)(31)(32), which represents a latent risk due to this virus incidence increase among children younger than five-years-old after the application of the rotavirus vaccine (33).…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Norovirus was identified in 3.5% of the analyzed samples with severe AGE, whereas other reports indicated a prevalence of 5.3% in Mexico (29). Despite this, different studies showed the prevalence of this pathogen to be up to 35.2% in sporadic outbreaks of acute gastroenteritis in children under five-years-old (30). Indeed, the GII genogroup has been found in up to 92% of the analyzed samples in other countries (30)(31)(32), which represents a latent risk due to this virus incidence increase among children younger than five-years-old after the application of the rotavirus vaccine (33).…”
Section: Discussionmentioning
confidence: 84%
“…Despite this, different studies showed the prevalence of this pathogen to be up to 35.2% in sporadic outbreaks of acute gastroenteritis in children under five-years-old (30). Indeed, the GII genogroup has been found in up to 92% of the analyzed samples in other countries (30)(31)(32), which represents a latent risk due to this virus incidence increase among children younger than five-years-old after the application of the rotavirus vaccine (33). Furthermore, the analysis revealed the presence of genotypes HAstV-1 and HAstV-3, indicating a high prevalence of astroviruses in this region, which is in line with reports from other countries (24,(34)(35)(36)(37).…”
Section: Discussionmentioning
confidence: 97%
“…The reason for this infection difference in diverse age groups was still ambiguous and further studies need to be conducted to explore the mechanism. [17,32,38,40,42].…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this different susceptibility to infection between diverse age groups is still unclear, and further studies need to be conducted to explore the mechanism of this difference. [17,32,38,40,42].…”
Section: Discussionmentioning
confidence: 99%